THE INFLUENCE OF SWIMMING ON MOTOR COORDINATION IN CHILDREN OF 3 TO 6 YEARS (Fiep Bulletin - online, 2014)
This study aims to analyze the influence of swimming on motor coordination in children of 3 to 6 years. 105 children from 3 to 6 years of age took part in the experiment and were divided into two groups: experimental group children who practiced swimming and; control group children who did not practice swimming. The experimental group was composed of 59 students who, as well as daily activities, practiced only swimming and who presented disturbance in motor coordination. The control group was composed of 46 students who presented these same disturbances and did not practice any physical activity apart from daily activities. Both the groups were selected for the pre-test in accordance with the protocol established by Lefèvre (1972). The program of infantile swimming was carried out for the experimental group two times per week for four months. After this period the children were re-evaluated using the same protocol (Lefèvre, 1972) for the post-test. In the analysis of motor coordination, significant differences were verified in the ages of 3, 4 and 6 years, where the experimental group showed more satisfactory results than the control group in the post-test. The children of 5 years obtained little improvement in motor development after practicing swimming and the data from this study suggest that experiments should be conducted with a larger sample for a new evaluation, using the same protocol.
Keywords: children; motor coordination; swimming